Development of Ionization waves in an Atmospheric‐Pressure Micro‐Plasma Jet. Issue 2 (February 2016) - Talviste, R.; Jõgi, I.; Raud, J.; Paris, P.
Abstract: Present study investigated the development of ionization waves in an atmospheric‐pressure plasma jet. Plasma was ignited by 6 kHz sinusoidal voltage applied to a cylindrical electrode surrounding the 500 μm inner diameter quartz tube and positioned 10 mm upstream from the tube orifice. The plasma current was observed using a plane electrode placed 20 mm downstream from the tube orifice. The spatial development of ionization waves was monitored by registering the optical emission along the axis of the tube. At voltages in range of 5.5 ‐ 7.5 kV only one pulse occurred during positive half‐period while at higher voltages the number of pulses increased up to 6 ‐ 7 per half‐period. The development of the first and subsequent pulses during one half‐period was essentially different. For the first pulse the sharp rise of optical emission characterizing the front of the ionization wave occurred initially near the high‐voltage electrode and moved towards the tube orifice and further in the He jet. The propagation of ionization wave coincided with the rise of the displacement current measured at the plane electrode. For subsequent ionization waves of the same half‐period, the emission occurred initially at the tube orifice and the ionization wave developed simultaneously in two directions: towards the high‐voltage electrode and towards the end of the jet. The velocity of ionization wave inside the tube was in range of (2. 5 ‐ 5.0) · 10 4 m/s for first wave and as high as 1.2 · 10 5 m/s for subsequent waves. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)